Ghostbusters (1984) [videorecording (DVD)] - Aykroyd, Dan; Aykroyd, Dan; Ramis, Harold; Ramis, Harold; Murray, Bill, 1950 September 21-; Weaver, Sigourney, 1949-; Moranis, Rick; Potts, Annie; Hudson, Ernie; Atherton, William (Columbia Pictures : Sony Pictures Home Entertainment, 2005)
When ghosts go on a rampage, only these men can save the world. Soon every spook in the city is loose and our heroes face the supreme challenge. If you want your spirits raised, who you gonna call? GHOSTBUSTERS.